Intergenerational Mobility and Macroeconomic History Dependence - Dilip Mokherjee; Stefan Napel (Aboa Centre for Economics (ACE), 2006)
That historical inequality can affect long run macroeconomic performance has been argued by a large literature on endogenous inequality using models of indivisibilities in occupational choice, in the presence of borrowing constraints. These models are characterized by a continuum of steady states, and absence of mobility in any steady state. We augment such a model with heterogeneity in agents abilities in order to generate occupational mobility in steady state. Steady states with mobility are shown to be generically locally unique and finite in number. We provide forms of heterogeneity for which steady state is globally unique, and others where they are non-unique. Agent heterogeneity may also cause competitive equilibrium dynamics to fail to converge, but convergence can be restored in the presence of sufficient inertia or occupation switching costs.
Keywords: D31; D91; E25; I21; J24; O11; O15; 330; Intergenerational mobility; occupational choice; human capital; borrowing constraints; inequality; history-dependence